The Relationship Between Professional Commitment and Work Motivation on Elementary School Teachers’ Performance - Dewi, Sumitra; Siahaan, Amiruddin; Hadijaya, Yusuf; Keling, Mansur (Jurnal Basicedu, 2023)
The teacher has the main role as a leader in the learning process. For this reason, teacher awareness of the importance of the profession and work motivation in improving teacher performance. This study aims to determine the relationship between professional commitment and work motivation on the performance of teachers in Medan city madrasas at the basic education level. In data analysis, this study used quantitative methods using a correlational approach, measured using a questionnaire instrument. Data analysis using descriptive statistics. This thesis uses a sample of 57 teachers in Madrasah Medan, Medan who were selected using the Slovin formula. The results of the study concluded that (1) there is a significant relationship between professional commitment to teacher performance, (2) there is a significant relationship between work motivation and teacher performance, and (3) there is a significant relationship between professional commitment and work motivation on teacher performance.